Effects of Different Nutrition Conditions on the Growth and Cadmium Accumulation of Landoltia punctata - GONG Zhihang; WANG Xianglian; XIE Huicui; ZHANG Tongtong; TANG Yuling; ZHAGN Yanyun; LIU Zilong; HU Liang; WEN jie; CHEN Ziming (Renmin Zhujiang)
In order to understand the effects of different nutrition conditions on the growth and cadmium accumulation of Landoltia punctata by treating the Landoltia punctata with Hoagland solution and Steinberg solution in different concentrations,the experiment were conducted with Hoagland (H) and Steinberg (S) nutrient solution concentrations at 0 (CK),0.1 (1/10 H,1/10 S),0.2 (1/5 H,1/5 S),and 1 (1 H,1 S),respectively,and Cd content at 0 mg/L,0.5 mg/L,5 mg/L and 10 mg/L,respectively.The growth index and Cd accumulation of Landoltia punctata were measured under different nutrition conditions.The results show that Landoltia punctata grows better in Hoagland solution,especially at 1/10 H concentration.After Cd treatment,the Cd accumulation in Steinberg condition is higher than that in Hoagland condition.In a word,the high nitrogen and phosphorus content could inhibit not only the growth of Landoltia punctata,but also the Cd accumulation in Landoltia punctata.The effect of nitrogen on Cd accumulation in Landoltia punctata varies with its different states.This study can provide guidance for the restoration of eutrophic water polluted by heavy metals of aquatic plants.